Application of the Open Source Business Model as a Tool for Corporate Renewal - Mrówka, Rafał (Wykorzystanie modelu biznesowego open source jako sposób odnowy organizacji, 2010)
The subject of this paper is the application of an open source business model for corporate renewal. At the beginning, it deals with the potential for commercial application of open source projects and demonstrates that it is by using these projects that businesses can in fact create a certain innovative business model for their operations. The paper then moves on to show the benefits that introduction of this business model can bring, and its relevance to corporate renewal programs. Finally, it identifies the areas not related to the creation of computer software in which business models resembling open source can be used.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 119-128
Keywords: open source; business model; corporate renewal